Emergency Ebola response: a new approach to the rapid design and development of vaccines against emerging diseases. Issue 3 (March 2015) - Tully, Claire M; Lambe, Teresa; Gilbert, Sarah C; Hill, Adrian V S
Summary: The epidemic of Ebola virus disease has spread at an alarming rate despite containment efforts. As a result, unprecedented large-scale international response efforts have been made in an attempt to gain control of the outbreak and reduce transmission. Several international consortia have been formed in a remarkable worldwide collaborative effort to expedite trials of two candidate Ebola virus vaccines: cAd3-EBOZ and rVSV-EBOV. In parallel, both vaccines are being manufactured in large amounts to enable future rapid deployment for management of the crisis.